Enriching experience: CDIM110's Training of Trainers at UiTM Kedah / Nor Hayati Kassim - Kassim, Nor Hayati (Perpustakaan Tun Abdul Razak, UiTM Sarawak, 2023)
The CDIM110 Training of Trainers program, organized by the School of Information Science at UiTM Campus Kedah on September 13th and 14th, 2023, was a remarkable event that brought together lecturers from various UiTM campuses, including Samarahan, Merbok, Segamat, Machang, and Rembau. The primary aim of this program was to deepen our understanding of six courses within the Diploma Information Management program, with the resource persons for these courses from UiTM Campus Kedah.